2020
DOI: 10.1111/ijun.12258
|View full text |Cite
|
Sign up to set email alerts
|

Testing and validation of the CIC‐cgQ and CIC‐childQ in paediatric patients and their caregivers

Abstract: Are the clean intermittent catheterization (CIC)‐cgQ and the CIC‐childQ feasible and generate valid measures of success performing CIC? CIC is the primary treatment for neurogenic bladder. However, instituting CIC with children can be challenging. Currently there are no validated instruments to measure the abilities of paediatric patients and their caregivers to perform CIC. The purpose of this study was to evaluate the validity and reliability of a modified version of the Intermittent Self Catheterization Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…A previous study identified and highlighted gaps in knowledge and management of this procedure, with limited tools to measure the quality of life of caregivers and children. The aforementioned research also emphasized the necessary participation and involvement of the health team and the family so as to improve knowledge and evidence-based care for a successful procedure 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study identified and highlighted gaps in knowledge and management of this procedure, with limited tools to measure the quality of life of caregivers and children. The aforementioned research also emphasized the necessary participation and involvement of the health team and the family so as to improve knowledge and evidence-based care for a successful procedure 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo realizado, identificou-se e destacou-se a existência de falhas no conhecimento e no manejo deste procedimento com limitadas ferramentas para a medição da qualidade de vida de cuidadores e crianças. A pesquisa supracitada reforçou, ainda, a necessária participação e envolvimento da equipe de saúde e da família no sentido de ampliar o conhecimento e o cuidado baseado em evidências para o sucesso do procedimento 4 .…”
Section: Introductionunclassified